A mini-review on biosurfactants from natural-based resources: sources, production, and application in oil industries / Mohammed Falalu Hamza ... [et al.] - Hamza, Mohammed Falalu; Ismail, Lukman; Hassan, Yarima Mudassir; Sikiru, Surajuddeen; Soleiman, Hassan; Imam, Saifullahi Shehu (Universiti Teknologi MARA Shah Alam, 2024)
Increasing energy demand and depletion of producing wells around the globe necessitate oil industries to seek alternative mechanisms to increase oil production. Among various chemical enhanced oil recovery (CEOR) unveiled today, surfactants have become indispensable chemical agents in oil industries because of their wide applications in both onshore and offshore operational activities. Unfortunately, considerable numbers of these surfactants are synthetic causing treatment and disposal of effluents uneconomical to oil industries. This arises due to strong legislation laws enforced by governing bodies to ensure cleaner and safer environments. Consequently, the search for biodegradable surfactants from natural-based resources has revolved around the oil industries aimed at reducing the impacts of synthetic products both environmentally and economically. Plants are widely recognised as natural resources to obtain biosurfactants from their naturally producing saponins. In addition, other chemical compounds derived directly from plant parts are converted to biosurfactants commonly referred to as green biosurfactants. However, researchers have expressed reservations about sustainable biosurfactant production from plants due to limited access to plant resources. The present review discusses the types, properties, sources, synthesis, and applications of biosurfactants in EOR. Furthermore, the paper presents prospects of biosurfactants in EOR and proposes a sustainable production mechanism.